Benzyl isothiocyanate improves the prognosis of Aspergillus fumigatus keratitis by reducing fungal load and inhibiting Mincle signal pathway - Yi, Wendan; Gu, Lingwen; Wang, Yuwei; Lin, Jing; Zhang, Lina; Wang, Qian; Diao, Weilin; Qi, Yinghe; Chi, Menghui; Yin, Min; Li, Cui; Zhao, Guiqiu (Frontiers in Microbiology, 2023)
Aspergillus fumigatus (A. fumigatus) keratitis is a potential blinding disease associated with A. fumigatus invasion and excessive inflammatory response. Benzyl isothiocyanate (BITC) is a secondary metabolite with broad antibacterial and anti-inflammatory activity extracted from cruciferous species. However, the role of BITC in A. fumigatus keratitis has not been discovered yet. This study aims to explore the antifungal and anti-inflammatory effects and mechanisms of BITC in A. fumigatus keratitis. Our results provided evidences that BITC exerted antifungal effects against A. fumigatus by damaging cell membranes, mitochondria, adhesion, and biofilms in a concentration-dependent manner. In vivo, fungal load and inflammatory response including inflammatory cell infiltration and pro-inflammatory cytokine expression were reduced in BITC-treated A. fumigatus keratitis. Additionally, BITC significantly decreased Mincle, IL-1β, TNF- and IL-6 expression in RAW264.7 cells that stimulated by A. fumigatus or Mincle ligand Trehalose-6,6-dibehenate. In summary, BITC possessed fungicidal activities and could improve the prognosis of A. fumigatus keratitis by reducing fungal load and inhibiting the inflammatory response mediated by Mincle.